1981
DOI: 10.1111/j.1476-5381.1981.tb09981.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Antagonists on the Alternation of the St‐t Complex and Associated Conduction Abnormalities During Coronary Occlusion in Dogs

Abstract: 1 The effects of Ca2+-antagonists on the relationships between alternate changes in the ST-T complex in the epicardial electrogram, ST-T alternans, and associated excitation-conduction abnormalities during coronary occlusion were examined in anaesthetized dogs. 2 Epicardial unipolar electrograms, bipolar electrograms (BPEG) and monophasic action potentials (MAP) were recorded with unipolar, composite and suction electrodes, respectively. 3 ST-T alternans was associated with serious conduction delay. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There have been a few animal studies conducted to examine the effect of anti-ischemic drugs on the occurrence of ST-T alternans during acute myocardial ischemia. Hashimoto, et al showed that calcium antagonists de-creased the incidence of ST-T alternans during acute myocardial ischemia, and Hayakawa, et al showed that diltiazem decreased the incidence of ST-T alternans and ventricular tachycardia/fibrillation during acute myocardial ischemia [8][9][10]20) . We have shown, by measuring extracellular K + , pH, and intramyocardial conduction time in an animal model, the anti-ischemic effect of verapamil [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few animal studies conducted to examine the effect of anti-ischemic drugs on the occurrence of ST-T alternans during acute myocardial ischemia. Hashimoto, et al showed that calcium antagonists de-creased the incidence of ST-T alternans during acute myocardial ischemia, and Hayakawa, et al showed that diltiazem decreased the incidence of ST-T alternans and ventricular tachycardia/fibrillation during acute myocardial ischemia [8][9][10]20) . We have shown, by measuring extracellular K + , pH, and intramyocardial conduction time in an animal model, the anti-ischemic effect of verapamil [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that calcium antagonists decrease both the rise in extracellular K + [K + ] e , and the fall in extracellular pH (pH e ), and previous studies have shown that calcium antagonists reduce the incidence of ST-T alternans during acute myocardial ischemia and decrease the incidence of ventricular fibrillation during ischemia [6][7][8][9][10] . We also have shown that ATP-sensitive K + channel opener pinacidil decreases the rise in [K + ] e and the fall in pH e that occur during acute myocardial ischemia 11) .…”
Section: Introductionmentioning
confidence: 99%
“…Ischaemic action potential duration alternans, reflecting cellular repolarization abnormalities, is probably the major cause of ischaemic T-wave alternans [17]. In one experimental study, severe conduction delay occurred concomitantly with episodes of alternans of action potential or ST segment elevation preceding ventricular arrhythmias, suggesting that re-entry is the mechanism of arrhythmia [18]. In another study that examined the role of ST alternans in the occurence of ventricular fibrillation after reperfusion in dogs, the magnitude of ST alternans increased progressively until ventricular fibrillation occurred.…”
Section: Discussionmentioning
confidence: 98%